Production Costs, Operating Costs, And Sales Volume Affect Net Profit - Suzan, Leny; Lumbantobing, Alfrina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The study's focus is on the food and beverage industry sub-sector between  2017to 2021, and it aims to examine the effect of production costs, operational costs, and sales volume on net profit. Purposeful sampling was used to choose a subset of 18 businesses for this investigation, yielding 90 observations. The findings show that production expenses, operational costs, and sales volume all have a role in the company's net profit. This phrase implies that in order to turn a profit, operating and production costs would rise in proportion to the volume of sales. Investors should think about these things while deciding how to allocate their funds.